Fabrikasi Kanal Mikro pada Substrat Akrilik menggunakan Laser Cutting CO2: Sudarsono, Gatut Yudoyono, Faridawati, Hasto Sunarno, Nurrisma Puspitasari, Yono Hadi Pramono - Sudarsono Sudarsono; Gatut Yudoyono Gatut Yudoyono; Faridawati Faridawati; Hasto Sunarno Hasto Sunarno; Nurrisma Puspitasari Nurrisma Puspitasari; Yono Hadi Pramono Yono Hadi Pramono (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2018)
CO2 laser cutting machine is a tool used in working on cutting and engraving some materials such as polymers, glass, paper, fabric and some non-metallic materials. CO2 laser cutting machines are widely used to make indoor and outdoor decoration such as nameplates in several shops, offices, hotels, companies, exhibition halls, and some accessories such as trophies, key chains and some other accessories. In this research will be studied about the influence of CO2 laser cutting speed on the shape, width, and depth in making a kanal mikro optical waveguide on acrylic substrate. The fabrication results were observed using an optical microscope as well as width and depth calculations usingmicrometer shifts. Fromthe results of observation and analysis of fabrication, the results showed that the higher the CO2 laser speed the shallower the depth of the resulting. In this study the power used 2.4W and produced kanal mikro with the smallest depth of 190.91 µm with laser speed 100 mm/s and biggest 604.17 µm with laser speed 50 mm/s. From the results of this study recommended a good speed to make kanal mikro as an optical waveguide application is 95 mm/s and 100 mm/s with a power of 2.4 W.